1991
DOI: 10.1093/jnci/83.4.260
|View full text |Cite
|
Sign up to set email alerts
|

Breast Self-Examination in Relation to the Occurrence of Advanced Breast Cancer

Abstract: Two hundred nine female enrollees of the Group Health Cooperative of Puget Sound who developed advanced-stage breast cancer during the period 1982-1988 were interviewed about their practice of breast self-examination (BSE), use of other breast cancer screening modalities, and medical and reproductive histories. Each subject's description of how she performed the examination was scored according to her mention of up to 10 recommended BSE techniques. A random sample of 433 women without advanced-stage breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
4

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(43 citation statements)
references
References 0 publications
0
38
1
4
Order By: Relevance
“…None of the case -control studies found statistically significant effects with only one suggesting a benefit (Harvey et al, 1997). The results for two of the case -control studies were not materially altered after adjustment for mammography use (Newcomb et al, 1991;Muscat and Huncharek, 1992). Table 3 provides the main results from the trials of teaching BSE and Figure 3 shows the relative risks and the pooled estimates for the main outcomes.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…None of the case -control studies found statistically significant effects with only one suggesting a benefit (Harvey et al, 1997). The results for two of the case -control studies were not materially altered after adjustment for mammography use (Newcomb et al, 1991;Muscat and Huncharek, 1992). Table 3 provides the main results from the trials of teaching BSE and Figure 3 shows the relative risks and the pooled estimates for the main outcomes.…”
Section: Resultsmentioning
confidence: 97%
“…The results were not materially different if the nonrandomised trial from the UK was excluded, pooled relative risk 1.05 (95% CI 0.90 -1.24, P ¼ 0.54). Or women with advanced breast cancer (Muscat, 1992;Newcomb, 1991). Dashes indicate that the data were not available from the published paper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em mulheres mais jovens ou mais idosas, entretanto, esse benefício ainda pode ser considerado controverso 7,13 . Quanto ao efeito do AEM utilizado como método de rastreamento, ensaios não-randomizados, estudos de coorte ou caso-controle evidenciaram que há uma relação inversa entre freqüência de realização do AEM e taxa de mortalidade 8,15 . Há dois grandes estudos randomizados em andamento com o intuito primário de avaliar o efeito do AEM na mortalidade por câncer de mama.…”
Section: Discussionunclassified
“…Women who practiced BSE with high proficiency did have a decreased risk of breast cancer deaths, but the retrospective design could not eliminate the possibility of recall bias. 42 Women do find breast cancers by self-examination. In women ages 40 to 45 years (before many have routine mammography), 65% of the cancers were self-detected.…”
mentioning
confidence: 99%